The Correlation between Knowledge Level of Women in Reproductive Age Couples Concerning Pap Smear with Pap Smear Test Services Utilization - Blandina Adrialisa Regina Roembiak; Heru Priyanto Samadi; Novi Primadewi (Nexus Kedokteran Klinik, 2015)
Background: In Indonesia, every year more than 15,000 cases of cervical cancer detected and approximately 8000 cases of which were fatal. The high prevalence of cervical cancer deaths in Indonesia may be caused by delays in diagnosis so that when detected, the disease has reached an advanced stage. Early detection of cervical cancer by Pap Smear is suitable method applied in developing countries because in addition to easy, cheap, effective, non-invasive. But in practice, these methods are still having problems such as doubt of the importance of examinations, lack of knowledge, and the fear of pain during the examination. The objective of this research is to know the correlation between knowledge level of women in Reproductive Age Couples (RAC) concerning Pap Smear with Pap Smear Test services utilization. Methods: The study design was analytic observational with cross sectional approach. The sample of this research was women in Reproductive Age Couples (RAC) in Gajahan Health Center, Surakarta. The number of samples were 90 people and were teken by simple random sampling tehnique. The people who was chosen as the sample are given the questionnaire, then they answered the question in the questionnaire. After the data collected, then the data was analyzed using Chi-Square test. (?2). Results: Percentage of women in Reproductive Age Couples who use VIA test services is 37.8%. Statistical tests using Chi-Square test performed on the variables which were knowledge level concerning Pap Smear with Pap Smear Test services utilization. Statistical test result value of the test statistic (?2) was 9.137 with a significance (p) of 0.003. P-value < 0.1 means that the confidence level of 90% or 10% significance level significant correlation both variables. Conclusions: There was a correlation between knowledge level of women in Reproductive Age Couples (RAC) concerning Pap Smear with Pap Smear Test services utilization. Women with higher knowledge concerning Pap Smear, lean to utilize Pap Smear test services. Keywords: knowledge level concerning Pap Smear, women in reproductive age couples, Pap Smear test services utilization.